ANALISIS AKRUAL DISKRESIONER, KETIDAKPASTIAN LINGKUNGAN OPERASI, DAN LEVERAGE DALAM MEMPREDIKSI LABA - SYAIFUDIN ZUHRI, ACHMAD (Jurnal Akuntansi AKUNESA, 2016)
This study aims to determine the effect of discretionary accruals, uncertain business environment and leverage on earnings persistence. The samples of this study are manufacturing companies listed on the Stock Exchange from 2000- 2014. There are 38 companies as samples where the total observation 190 companies. This study uses three independent variables. The first is discretionary accruals are measured by the net change in operating assets deflated by average total assets. The second is uncertain business environment that is proxied by cash flows volatility, sales volatility and operating cycle. The last variable is leverage that proxied by debt to assets ratio. The hypothesis is tested using multiple linear regression.  The results showed that, cash flow volatility and sales volatility influence earnings persistence. However, debt to equity ratio, discretionary accruals and operating cycles not. This means that not all information in financial statements can be used to predict next period earnings or to forecast earnings/earnings persistence.